Efficiency Analysis of Tertiary Channels in Mataram Irrigation. Special Region of Yogyakarta - Murtaqi, Muhamad Anif Ainul; Wignyosukarto, Budi Santoso; Nurrochmad, Fatchan (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Mataram irrigation canal is an agricultural infrastructure built around 1942 with a channel length of ± 34.5 km. Changes in land use patterns that occur in Yogyakarta will certainly have an impact on changing the demand for water discharge in the canals and the ability of the canals to drain water. The tertiary network in the Mataram irrigation canal is the most influential on land use change. where the network connects the Mataram main network with the surrounding rice fields. This study reviews how much efficiency and water loss occurs in the Mataram irrigation tertiary channel. Analysis of the efficiency of the Mataram irrigation canal was carried out by comparing the discharge inflow and outflow in the channel while the analysis of water loss in the channel is carried out by calculating the amount of evaporation and seepage that occurs in the channel. Efficiency results in 25 Mataram tertiary channels. there are 9 channels where water utilization is greater than water demand indicated loss that occurs in the channel. Loss in the channel is caused using water for other factors or water leakage occurs in the channel. This is indicated by the fact that the water supplied to the canal is greater than the required amount of water. so that the percentage of water usage in this channel is more than 100%. Different conditions were obtained from the other 16 canals. where water utilization was less than the water requirement. so there was excess water in the canals. This incident occurred because the irrigation service area had experienced a change in land use or a lot of land that did not need water. This causes the downstream water discharge to be greater than the given discharge because there is additional discharge from other sources.